2022
DOI: 10.1128/spectrum.01769-21
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bacterial Detection in Urine Using Laser Scattering and Deep Learning Analysis

Abstract: This study performed deep learning of multiple laser scattering patterns by the bacteria in urine to predict positive urine culture. Conventional urine analyzers have limited performance in identifying bacteria in urine. This novel method showed a satisfactory accuracy taking only 30 min of analysis without conventional urine culture. It was also developed to predict the Gram staining reaction of the bacteria. It can be used as a standalone screening tool for urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…It was stated that 263 test images were used during the experiments. It was reported that the proposed method reaches 90.9% accuracy even at low bacterial density [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that 263 test images were used during the experiments. It was reported that the proposed method reaches 90.9% accuracy even at low bacterial density [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers use AI for bacterial detection. Lee et al developed a method for rapid detection of bacteria in urine using laser scattering combined with deep learning analysis ( 24 ). Wang et al indicated that a combination of Raman spectroscopy and deep learning algorithms can accurately identify bacteria at the genus and species levels ( 25 ).…”
Section: Introductionmentioning
confidence: 99%